Benefits from the implementation of project tasks with the use of virtual team = Korzyści z realizacji zadań projektowych z wykorzystaniem zespołu wirtualnego - Barnowska, Beata; Kozaryn, Maciej (Zielona Góra: Faculty of Economics and Management Press)
The necessity of customer oriented approach, the ability of quick adapting to changing demand and the expectations of reducing project costs have recently resulted in a strong development of cooperation between various organizations implementing joint ventures. Projects-oriented organizations, creating virtual project teams, have become more and more popular. Dissemination of this organizational form has induced the authors to consider the real benefits achieved by enterprises using virtual project teams to implement projects.
Keywords: zespół wirtualny; projektowanie; zarządzanie projektami; wirtualny zespół projektowy; virtual team; projects; project management; virtual project team